(untitled) (Research, Society and Development, 2019)
The Portuguese language spoken in Brazil is evolving with social influences. The purpose of this study is to verify the incidence of language addiction, specifically the use of the term "type", among young university students of a Brazilian university. An online survey was conducted to find out the most common language addictions among students and the frequency with which they occur in speech. The data showed that the term "type" is among the most spoken among informants, second only to the terms "vei" and "mano" and is associated with the idea of uncertainty, unpreparedness, vice or imitation and lack of vocabulary expansion. One can conclude that there is an urgent need to intervene in communicative and linguistic practices in schools so that there is a change in the use of language addictions, especially among the public studied.